Analisis Performansi Modifikasi Binary Spray and Wait menggunakan Prophet pada DTN - Adhiguna, Bima; Wibowo, Tody Ariefianto; Yovita, Leanna Vidya (JURNAL NASIONAL TEKNIK ELEKTRO, 2017)
Delay Tolerant Network (DTN) enabling communication in an environment where there may be no link end-to-end, communication opportunities come and go and the intervals can be extremely long and even previously unknown. There are some Routing Protocol on DTN, including Binary Spray and Wait is a development of Spray and Wait, and PROPHET.Â  Research discuss about modification of Binary Spray and Wait in spray phase using delivery predictability in PROPHET. Simulation used ONE (Opportunistic Network Environtment) Simulator and analyze Delivery Probability, Overhead Ratio, Buffer Time, Average Latency and Average Remaining Energy in Shortest Path Map Based dan Random Way Point movement. Based on observation, the resulting modification of Binary Spray and Wait improve performance and buffer time average latency compared with Binary Spray and Wait, but slightly lower probability delivery and improving overhead ratio.Keywords : Delay Tolerant Network, Spray and Wait, PROPHET, Shortest Path Map Based, Random Way Point.AbstrakDelay Tolerant Network (DTN) memungkinkan komunikasi dalam lingkungan di mana mungkin tidak ada jalur end-to-end, peluang komunikasi datang dan pergi dan intervalnya bisa sangat panjang dan bahkan tidak diketahui sebelumnya. Ada beberapa Routing Protocol pada DTN, diantaranya Binary Spray and Wait yang merupakan pengembangan dari Spray and Wait, dan PROPHET. Penelitian ini membahas tentang modifikasi Binary Spray and Wait pada tahap spray menggunakan teknik delivery predictability yang ada di PROPHET. Simulasi menggunakan ONE (Opportunistic Network Environtment) Simulator dan menganalisa Delivery Probability, Overhead Ratio, Buffer Time, Average Latency dan Average Remaining Energy pada pergerakan node Shortest Path Map Based dan Random Way Point. Berdasarkan pengamatan, dihasilkan Modifikasi Binary Spray and Wait meningkatkan performansi average latency dan buffer time dibanding dengan Binary Spray and Wait, namun menurunkan sedikit delivery probability dan memperbesar overhead ratio.Kata Kunci : Delay Tolerant Network, Spray and Wait, PROPHET, Shortest Path Map Based, Random Way Point.